Aplikasi SABARSON (Si Penjaga Kualitas Rumah Sakit) Sebagai Early Warning System: SABARSON Application: The Guardian Of Hospital Quality As An Early Warning System - Alfina Lailatul Maghfiroh; Umi Khoirun Nisak (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Determining the quality of hospital service is about the efficiency of bed management. In some hospitals, Barber Johnson graphs are still described in Microsoft Excel, but the BOR indicator has not been displayed. SABARSON: The Guardian of Hospital Quality as an Early Warning System is a creative innovation in system design that can be used to determine the quality of a hospital by displaying a graph of the four indicators BOR, LOS, BTO, and TOI. This type of design uses the system development method with the development life cycle (SDLC) approach with the stage of problem identification, reference search, dataflow and concept preparation, color palette preparation, system design, and system implementation. The purpose of this study is to help and facilitate medical record workers in describing or displaying a Barber Johnson graph quickly and precisely. This study resulted in several interface design results such as login, BOR, TOI, LOS, BTO, report recapitulation, and Barber Johnson graphic.